Elastic scattering in image-potential bands observed by two-photon photoemission - Boger, Klaus; Fauster, Thomas; Weinelt, Martin (New Journal of Physics, 2005)
Adsorbate atoms on surfaces cause considerable scattering of electrons. In image-potential bands, elastic scattering rates can be determined by measuring the linewidth in angle-, time- and energy-resolved two-photon photoelectron spectroscopy. From these data, the total cross section for elastic scattering of electrons in the first image-potential band on the Cu(0 0 1) surface by statistically distributed Cu adatoms has been determined. For large parallel momenta of the electron, the scattering by an adatom can be described by a dipole potential.